Assessing shortnose sturgeon response to estuarine dredging in the Savannah River using a before-after control-impact (BACI) approach - Hunter J. Rider; Katie M. Morgan; Alan T. Bond; Joseph D. Nolan; Adam G. Fox; Martin J. Hamel (Environmental Biology of Fishes, 2026)
Estuaries are productive ecosystems that support diverse aquatic species and human economies through fisheries, recreation, and navigation. However, coastal development and dredging have altered the ecological processes of estuarine habitats. In the Savannah River estuary, the Savannah Harbor Expansion Project (SHEP) deepened the river’s navigational channel by dredging to amplify vessel commerce. The endangered shortnose sturgeon ( Acipenser brevirostrum ) relies on estuarine habitat in the Savannah River to complete its life cycle; the SHEP dredging was predicted to decrease estuarine habitat availability for the local population of shortnose sturgeon. To assess population trends in relation to the SHEP, we conducted mark-recapture sampling for shortnose sturgeon in the Savannah River in the summers of 2013–2024 and used Huggins closed population capture-recapture models to estimate annual juvenile and adult abundances. We applied a before-after control-impact (BACI) model approach to compare changes in demographic-based abundances over time in the Savannah River to abundances in the geographically proximate, relatively unaltered Altamaha River. The BACI model indicated a significant decline in juvenile abundance in the Savannah River during and after the SHEP, while adult abundance remained unchanged. The timeframe of this decline and the absence of juvenile declines in the reference river suggest it may be associated with dredging via the SHEP. Juvenile declines may further threaten recovery of the Savannah River population. Continued population-level monitoring efforts and protection of the remaining estuarine habitat are critical for the long-term persistence of the Savannah River shortnose sturgeon population.